Social entrepreneurs on the periphery: Uncovering emerging pioneers of regional development. - Christmann, Gabriela B. (Routledge, 2014)
This contribution deals with the initiatives of social entrepreneurs who are particularly breaking new ground in the field of regional development - an item that has not yet been discussed in literature. On the basis of an exploratory study, it will analyze four selected projects in Europe (Spain and Germany) where social entrepreneurs started bottom-up initiatives in regional development. In this context, it will mainly pursue the questions of how the entrepreneurs managed to do this, that is, how they addressed existing problems, how they acted, how their (innovative) projects worked, and what implications their projects have for socio-spatial development. It will be shown how social entrepreneurs try to empower (entrepreneurial) citizens by providing help for self-help, particularly by way of educational offers, counseling and coaching, and by supporting citizens to establish useful contacts and social networks; not least by organizing financial means, usually in the form of micro-loans.
Keywords: Regionalplanung; Regionale Disparität; Randzone; Ländlicher Raum; Regionalentwicklung; Regionalwirtschaft; Unternehmen; Wirtschaftsförderung; Peripherie; Strukturschwäche; Soziales Unternehmen; Modellprojekt